The practice of coastal management initiatives in using geographical information system in Selangor, Malaysia - Paiman, Tuminah; Asmawi, M. Zainora (2015)
Globally, coastlines are undergoing rapid development and firm management policies have to be established. However, for any shore management to be effective, the policies need to be based on informed decision-making. GIS encourages the development and use of standards for coastal data definition, collection and storage, which promotes compatibility of data and processing techniques between projects and departments, as well as ensuring consistency of approach at any one site over time. Purpose of this research to gather a perception from government agencies that has used GIS in managing coastal area in Selangor. Two main divisions of coastal change analysis may be recognized: monitoring and simulation modelling. GIS modelling and simulation of coastal phenomena are extremely valuable techniques for assessing the effectiveness and likely impacts of such intervention. Thus, a well-designed coastal area information system could be a significant decision support tool to aid the development of integrated and sustainable coastal resource management strategies.